Polyurethane high-refraction optical material as well as preparation method and application thereof
Through the chemical moisture curing reaction of isocyanate and polyol and the compounding of inorganic nanoparticles, the existing high-refractive index optical materials have been solved, and the existing high-refractive index optical materials have high density, few types, high cost and poor dispersion during processing and forming, and a polyurethane optical material with high refractive index, good dispersion and stability is achieved, and is suitable for optical film materials of modern electronic equipment.
Patent Information
- Application Number
- CN202311251366.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing high-refractive index optical materials have problems such as high density, few types, high cost and poor dispersion during processing and forming, which is difficult to meet the demand for optical film materials of modern electronic equipment.
The chemical moisture curing reaction is used with isocyanate and polyol to produce a highly crosslinked polyurethane polymer, and by combining with inorganic nanoparticles, using the low viscosity of alcohol or amine monomer and the active hydrogen groups of the polyol, it achieves good dispersion without the need for additional dispersion aids.
It achieves high refractive index, good dispersion and stability, reduces production costs, broadens the application range of materials, and is suitable for optical material layers of OLED, Mini LED, Micro LED and LCD display devices.
Smart Images

Figure BDA0004470345080000021 
Figure BDA0004470345080000121 
Figure FDA0004470345070000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a polyurethane high-refractive optical material and a preparation method and application thereof. Background Art
[0002] In modern materials science and technology, optical materials have become one of the most important components and have been widely used in many fields such as electronics, automobiles, building materials, coating devices, and information. Traditional optical materials mainly include two categories: inorganic optical materials and organic optical materials. Although inorganic optical materials have excellent characteristics such as high mechanical properties, high refractive index, and good optical transparency, traditional inorganic optical materials are gradually replaced by organic optical materials with excellent characteristics such as low density, easy processing, impact resistance, many types, and good optical properties due to their disadvantages such as difficulty in processing and molding, high density, and few types. Organic optical resins are widely used in the field of optical films, mainly in optical lenses and displays.
[0003] According to the different refractive indices of optical materials, organic optical materials can be divided into high refractive index optical materials and low refractive index optical materials. In order to meet the requirements of ultra-thin lenses, reducing mass and curvature, and improving the performance of optical devices, and making liquid crystal displays brighter, it is necessary to improve the refractive index performance of optical film materials.
[0004] Optical materials with high refractive index can effectively reduce the thickness and curvature of devices. Therefore, improving the refractive index of polymer optical materials is one of the main research directions of optical materials. At present, in order to develop polymers with high refractive index, atoms or groups with high molar refractive index and low molar volume can be introduced into polymer materials, or optical materials can be mixed with inorganic nanoparticles with high refractive index. Due to the quantum size effect, inorganic nanoparticles make nanocomposites have good toughness, rigidity and mechanical strength. However, due to the high viscosity of the resin and the small size of the nanoparticles, it is not easy to disperse, and it is easy to agglomerate in the resin. Therefore, it is often necessary to modify the surface of the inorganic nanoparticles or add volatile, low-viscosity solvents or dispersants to make them dispersed evenly, which increases production costs and affects the panel yield. Therefore, it is imperative to provide a solvent-free high refractive index material with good system dispersibility. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a polyurethane high-refractive optical material and a preparation method and application thereof.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 15 to 30 parts of isocyanate, 10 to 20 parts of active hydrogen compound, 25 to 60 parts of inorganic nanoparticles, and 0.1 to 3 parts of catalyst; the isocyanate is selected from at least one of aliphatic isocyanate, alicyclic isocyanate, and aromatic isocyanate; the active hydrogen compound is a polyol.
[0007] By adopting the above technical solution, the reactive groups in the isocyanate react with the alcohol containing active hydrogen to undergo a chemical wet curing reaction to generate carbamate groups, and finally form a polyurethane polymer with a highly cross-linked network structure, which has excellent properties such as high bonding strength, wear resistance, high temperature resistance, water resistance and solvent resistance. When used as an optical material, water vapor intrusion reacts with the isocyanate group to further increase the degree of cross-linking, achieve water and oxygen barrier effects, and improve the overall stability of the resin.
[0008] When compounded with fillers such as inorganic nanoparticles, the viscosity of alcohol or amine monomers is low, and they have good dispersibility when mixed with inorganic nanoparticles, without the need for additional dispersing agents. Moreover, polyols, polyamines, etc. are rich in active hydrogen groups, which can more easily form chemical bonds with inorganic nanoparticles, thereby improving the overall uniformity of the system. When compounded with inorganic nanoparticles, they can effectively increase the refractive index, thermal conductivity, aging resistance, etc. of polyurethane-based high-refractive optical materials, thereby broadening the application range of the products.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Furthermore, the isocyanate has a structure shown in formula (1):
[0011]
[0012] wherein Ar is selected from unsubstituted or substituted C1-C5 alkyl, C1-C5 alkyl with ether bond block, keto group, hydroxyl group, etc. 15 Alkyl, C3-C 20 Cycloalkyl, C6-C 20 Aryl; the C6-C 20 The aryl group contains 1 to 3 benzene rings, which are connected by single bonds, C1-C3 alkyl groups or fused groups; n is an integer of 1 to 3.
[0013] Ar is selected from unsubstituted or substituted C1-C5 alkyl, C1-C5 alkyl with ether bond block, keto group, hydroxyl group and at least one of C1-C5 alkyl. 15 Alkyl, C3-C 20 When the cycloalkyl group is added, no benzene ring conjugated quinone-type chromophore is generated, and the obtained optical material has better yellowing resistance and better durability.
[0014] Furthermore, the C1-C 15 The alkyl group is selected from propane, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, n-pentyl, 2-pentyl, 3-pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl or nonane; the C3-C 20 The cycloalkyl group is selected from cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclononane, cyclodecane, cyclododecane, cyclotetradecane or cyclohexadecane; the C6-C 20 The aryl group is selected from benzene ring, naphthalene, anthracene, biphenyl, diphenylmethane, diphenylethane or triphenylmethane. 20 In the case of an aryl group, the hydrogen on the benzene ring is replaced by the reactive isocyanate functional group.
[0015] Further, the isocyanate is selected from methyl isocyanate, ethyl isocyanate, propyl isocyanate, amyl isocyanate, hexyl isocyanate, heptyl isocyanate, octyl isocyanate, cyclopropyl isocyanate, cyclobutyl isocyanate, cyclopentyl isocyanate, cyclohexyl isocyanate, cycloheptyl isocyanate, cyclooctyl isocyanate, cyclododecyl isocyanate, cyclohexylethyl isocyanate, 4-hydroxycyclohexyl isocyanate, 4-ketocyclohexane isocyanate, 4-methoxycyclohexyl isocyanate, At least one of alkyl isocyanate, phenyl isocyanate, 4-pentylphenyl isocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 1,8-octyl diisocyanate, 1,4-cyclohexane diisocyanate, 1,4-cyclohexane dimethyl diisocyanate, p-phenylene diisocyanate, m-phenylenedimethyl isocyanate, p-methoxyphenyl isocyanate, toluene-2,5-diisocyanate, naphthalene diisocyanate, anthracene diisocyanate, and triphenylmethane triisocyanate.
[0016] Further, the polyol is at least one of polyester polyol or polyether polyol;
[0017] The polyether polyol is an addition polymerization product obtained by performing addition polymerization reaction on at least one of ethylene glycol, propylene glycol, glycerol, glycerine, pentaerythritol, sorbitol, sucrose, bisphenol A or toluene diamine and at least one of ethylene oxide, propylene oxide or tetrahydrofuran; or the polyether polyol is a homopolymer or copolymer of ethylene oxide, propylene oxide or tetrahydrofuran monomers;
[0018] Polyester polyols are condensation products of dibasic acids such as adipic acid, 1,4-succinic acid, and terephthalic acid with diols such as ethylene glycol, ethylene glycol, propylene glycol, and 1,4-butanediol;
[0019] Furthermore, the polyether polyol is selected from at least one of polyoxypropylene glycol, polytetramethylene glycol, and tetramethylene glycol-oxypropylene copolymer glycol; the polyester polyol is selected from at least one of polyethylene adipate, polyethylene adipate propylene glycol, polyethylene terephthalate, and phthalic anhydride polyester polyol.
[0020] By adopting the above technical scheme, polyester polyol contains a large number of ester groups, has strong polarity, and has high relative cohesive energy, and the obtained polyurethane has excellent bonding performance, good heat resistance, and good oil resistance; polyether polyol contains a large number of ether bonds and is not easy to hydrolyze, and the obtained polyurethane has excellent hydrolysis resistance, good low temperature resistance and high molecular chain flexibility; if polyols are compounded and used, the content of ester groups and ether groups as well as soft segments and hard segments can be adjusted, thereby adjusting the flexibility and adhesion of optical materials.
[0021] Furthermore, the inorganic nanoparticles are selected from any one or more combinations of Si3N4, NiO, Al2O3, ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, and Nd2O3.
[0022] Furthermore, the catalyst is selected from one or more combinations of organic amine catalysts and organic metal catalysts;
[0023] The organic amine catalyst is selected from at least one of triethylamine, triethylenediamine, N,N-dimethylcyclohexylamine, N,N-diethylpiperazine, triethanolamine, N,N-dimethylpyridine, and dimorpholine diethyl ether;
[0024] The organic metal catalyst is selected from at least one of zinc isooctanoate, bismuth isooctanoate, dibutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, stannous oleate, stannous chloride, tetra-n-butyltin, hydroxytrimethyltin, and dibutyltin dilaurate.
[0025] By adopting the above technical solution, the organotin catalyst in the organometallic catalyst is selective for the reaction between isocyanate and water or alcohol. Tin can accelerate the reaction between isocyanate and alcohol, but has little catalytic effect on cyanate and water; while the tertiary amine compounds in the organoamine catalyst can catalyze the reaction between isocyanate and water or alcohol at the same time. In this solution, the organotin catalyst is preferred.
[0026] Furthermore, it also includes one or more combinations of antioxidants, tackifying resins, and chain extenders.
[0027] Furthermore, the antioxidant is selected from at least one of antioxidant 264, antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, and 2,6-di-tert-butyl-4-methylphenol;
[0028] The tackifying resin is selected from at least one of rosin, terpene resin, alkylphenolic resin, xylene resin, and rosin glycerol ester;
[0029] The chain extender is selected from at least one of diethylene glycol, triethylene glycol, cyclohexanedimethanol, ethylene glycol, propylene glycol, hexanediol, butanediol, neopentyl glycol, triethylene glycol, dipropylene glycol, and ethyl hexanediol.
[0030] A method for preparing the above-mentioned polyurethane high-refractive optical material comprises the following steps:
[0031] S1, placing active hydrogen compound and inorganic nanoparticles in a flask, heating while stirring, controlling the reaction temperature at 80-85°C, evacuating the flask to an absolute pressure of 50-100 Pa, continuing to heat to 120-130°C, and maintaining the reaction temperature and absolute pressure for 0.4-0.6h; then filling the flask with nitrogen to break the vacuum state, and cooling the flask to 80-85°C;
[0032] S2, adding isocyanate and catalyst into a flask, evacuating the flask to an absolute pressure of 50-100 Pa, controlling the reaction temperature in the flask to 70-95° C., maintaining the pressure and temperature conditions and continuing the reaction for 1.5-3 hours;
[0033] S3, after the reaction is completed, nitrogen is filled into the flask to break its vacuum state, and the flask is evacuated again until the absolute pressure in the flask is 50-100Pa, the reaction temperature in the flask is controlled to be 85-90°C, and the reaction is carried out for 1-3h to obtain a polyurethane high-refractive optical material.
[0034] An application of the above-mentioned polyurethane high-refractive optical material in preparing an optical material layer of a display device. In particular, it is used to prepare OLED, Mini LED, Micro LED and LCD display devices. Specifically, it can be prepared by coating, spraying, spin coating, scraping (wire rod), nanoimprinting, inkjet printing, screen printing or pad printing, and used as a light extraction layer in OLED, Mini LED, Micro LED and LCD displays.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] Polyurethane optical materials are prepared by mixing isocyanate and polyol monomers with low viscosity. Before the reaction, inorganic nanoparticles are mixed with isocyanate and polyol, which is conducive to the full mixing and dispersion of various raw materials and improves the degree of reaction. And because polyols contain a large number of active hydrogen groups, it is easier to form hydrogen bonds with inorganic nanoparticles. During the mixing reaction, there is no need to add additional volatile, low-viscosity solvents / dispersants, or modify the surface of inorganic nanoparticles to disperse them evenly, which controls costs and effectively improves the uniformity of the system, thereby improving the refractive index, tensile strength and other properties of optical materials; due to the hygroscopicity of isocyanate groups in polyurethane, they can react with invading water vapor, further increasing the degree of cross-linking, thereby achieving water and oxygen barrier effects while improving the overall stability of the resin. DETAILED DESCRIPTION
[0037] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0038] In the embodiment, the inorganic nanoparticles are added in the form of being mixed with a commercially available dispersant: the dispersing solvent is commercially available PGMEA (propylene glycol methyl ether acetate), and the wt% of the inorganic nanoparticles is 40-60%. In this embodiment, the mass fraction of the inorganic nanoparticles is 50%.
[0039] Embodiment 1:
[0040] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 15 parts by weight of cyclopentyl isocyanate, 10 parts by weight of polytetramethylene glycol, 25 parts by weight of TiO2, 0.1 parts by weight of dibutyltin dilaurate, 0.1 parts by weight of antioxidant 264, 0.1 parts by weight of rosin glycerol ester, and 1 part by weight of hexanediol.
[0041] Preparation of polyurethane optical materials:
[0042] S1: Add weighed polyols, inorganic nanoparticles, antioxidants, tackifiers, and chain extenders into a three-necked flask, turn on the heating device and agitator, control the reaction temperature at 80°C, evacuate the flask to an absolute pressure of 70Pa, continue heating to 120°C, and maintain this temperature and absolute pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the three-necked flask with high-purity nitrogen to break the vacuum, and cool it down to 80°C;
[0043] S2: Under nitrogen protection, weighed isocyanate and catalyst are added into a three-necked flask in sequence, the nitrogen control switch is turned off, the vacuum pump and the stirrer are turned on, the absolute pressure in the flask is controlled to 80Pa, the reaction temperature in the three-necked flask is controlled to 80°C, and the reaction is continued for 2h under this condition;
[0044] S3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the three-necked flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85℃, and react for 2h to obtain a polyurethane high-refractive optical material.
[0045] Embodiment 2:
[0046] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 30 parts by weight of cyclopentyl isocyanate, 20 parts by weight of polytetramethylene glycol, 25 parts by weight of ZrO2, 1 part by weight of triethylamine, 1 part by weight of antioxidant 1010, 1 part by weight of rosin glycerol ester and 3 parts by weight of diethylene glycol.
[0047] The preparation method is the same as that in Example 1.
[0048] Embodiment 3:
[0049] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 20 parts by weight of cyclohexyl isocyanate, 15 parts by weight of polytetramethylene glycol, 30 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 2 parts by weight of diethylene glycol.
[0050] The preparation method is the same as that in Example 1.
[0051] Embodiment 4:
[0052] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 10 parts by weight of octyl isocyanate, 20 parts by weight of cyclopentyl isocyanate, 10 parts by weight of polytetramethylene glycol, 10 parts by weight of polyethylene adipate, 30 parts by weight of TiO2, 0.5 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester and 2 parts by weight of diethylene glycol.
[0053] The preparation method is the same as that in Example 1.
[0054] Embodiment 5:
[0055] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of 4-methoxycyclohexane isocyanate, 17 parts by weight of polyethylene glycol propylene glycol adipate, 28 parts by weight of ZrO2, 0.4 parts by weight of dibutyl tin dilaurate, 0.3 parts by weight of antioxidant 264, 0.4 parts by weight of rosin glycerol ester, and 2.5 parts by weight of diethylene glycol.
[0056] The preparation method is the same as that in Example 1.
[0057] Embodiment 6:
[0058] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of 4-hydroxycyclohexyl isocyanate, 17 parts by weight of polyethylene glycol propylene glycol adipate, 28 parts by weight of ZrO2, 0.4 parts by weight of dibutyl tin dilaurate, 0.3 parts by weight of antioxidant 264, 0.4 parts by weight of rosin glycerol ester, and 2.5 parts by weight of diethylene glycol.
[0059] The preparation method is the same as that in Example 1.
[0060] Embodiment 7:
[0061] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of phenyl isocyanate, 13 parts by weight of polyoxypropylene glycol, 30 parts by weight of ZrO2, 0.5 parts by weight of triethanolamine, 0.5 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 1.5 parts by weight of diethylene glycol.
[0062] The preparation method is the same as that in Example 1.
[0063] Embodiment 8:
[0064] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of 4-ketocyclohexane isocyanate, 17 parts by weight of polyethylene glycol propylene glycol adipate, 28 parts by weight of ZrO2, 0.4 parts by weight of dibutyl tin dilaurate, 0.3 parts by weight of antioxidant 264, 0.4 parts by weight of rosin glycerol ester, and 2.5 parts by weight of diethylene glycol.
[0065] The preparation method is the same as that in Example 1.
[0066] Embodiment 9:
[0067] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 18 parts by weight of hexamethylene diisocyanate, 13 parts by weight of polytetramethylene glycol, 28 parts by weight of ZrO2, 0.4 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 264, 0.4 parts by weight of rosin glycerol ester, and 2.5 parts by weight of diethylene glycol.
[0068] The preparation method is the same as that in Example 1.
[0069] Embodiment 10:
[0070] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 20 parts by weight of 1,4-cyclohexane diisocyanate, 15 parts by weight of polytetramethylene glycol, 30 parts by weight of ZrO2, 0.5 parts by weight of dibutyltin dilaurate, 0.3 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 2 parts by weight of diethylene glycol.
[0071] The preparation method is the same as that in Example 1.
[0072] Embodiment 11:
[0073] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of p-phenylene diisocyanate, 13 parts by weight of polyoxypropylene glycol, 30 parts by weight of ZrO2, 0.5 parts by weight of triethanolamine, 0.5 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 1.5 parts by weight of diethylene glycol.
[0074] The preparation method is the same as that in Example 1.
[0075] Embodiment 12:
[0076] A polyurethane high-refractive optical material comprises the following raw materials in parts by weight: 25 parts by weight of triphenylmethane triisocyanate, 13 parts by weight of polyoxypropylene glycol, 30 parts by weight of ZrO2, 0.5 parts by weight of triethanolamine, 0.5 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 1.5 parts by weight of diethylene glycol.
[0077] The preparation method is the same as that in Example 1.
[0078] Comparative Example 1:
[0079] A polyurethane optical material comprises the following raw materials in parts by weight: 20 parts by weight of cyclohexyl isocyanate, 15 parts by weight of polytetramethylene glycol, 30 parts by weight of ZrO2, 50 parts by weight of propylene glycol methyl ether acetate, 0.5 parts by weight of dibutyl tin dilaurate, 0.3 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 2 parts by weight of diethylene glycol.
[0080] Preparation of polyurethane optical materials:
[0081] S1: Add weighed polytetrahydrofuran diol, antioxidant 264, rosin glycerol ester and diethylene glycol into a three-necked flask according to the proportion, turn on the heating device and the stirrer, control the reaction temperature at 80°C, evacuate the flask to an absolute pressure of 70Pa, continue to heat to 120°C, and maintain this temperature and pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, and cool it to 80°C;
[0082] S2: Under nitrogen protection, weighed cyclohexyl isocyanate and dibutyltin dilaurate amine were added into a three-necked flask in sequence, the nitrogen control switch was turned off, and the vacuum pump and agitator were turned on to control the absolute pressure in the three-necked flask to 80 Pa, and the temperature of the reactants in the flask to 80° C. The reaction was maintained under this condition for about 2 hours;
[0083] S3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the three-necked flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85℃, and react for about 2h to obtain the polyurethane resin.
[0084] S4: Add the polyurethane resin, propylene glycol methyl ether acetate and ZrO2 obtained in step S3 into a three-necked flask, turn on the heating device and the stirrer, and stir evenly.
[0085] Since the polyurethane resin has a high viscosity (>2000cps), it cannot be directly used for optical materials. Therefore, the raw materials of the polyurethane optical material in this comparative example are based on those in Example 3 and a solvent component (propylene glycol methyl ether acetate) is added.
[0086] Comparative Example 2:
[0087] A polyurethane optical material comprises the following raw materials in parts by weight: 25 parts by weight of phenyl isocyanate, 13 parts by weight of polyoxypropylene glycol, 30 parts by weight of ZrO2, 50 parts by weight of propylene glycol methyl ether acetate, 0.5 parts by weight of triethanolamine, 0.5 parts by weight of antioxidant 264, 0.5 parts by weight of rosin glycerol ester, and 1.5 parts by weight of diethylene glycol.
[0088] Preparation of polyurethane optical materials:
[0089] S1: Add weighed polyoxypropylene glycol, antioxidant 264, rosin glycerol ester and diethylene glycol into a three-necked flask according to the proportion, turn on the heating device and the stirrer, control the reaction temperature at 80°C, evacuate the flask to an absolute pressure of 70Pa, continue heating to 120°C, and maintain this temperature and pressure for 0.5h to remove trace moisture in the reactants; turn on the nitrogen control switch, slowly fill the flask with high-purity nitrogen to break the vacuum, and cool it down to 80°C;
[0090] S2: Under nitrogen protection, weighed cyclohexyl isocyanate and triethanolamine were added into the three-necked flask in sequence, the nitrogen control switch was turned off, the vacuum pump and the stirrer were turned on, the absolute pressure in the three-necked flask was controlled to 80Pa, the temperature of the reactants in the three-necked flask was controlled to 80°C, and the reaction was maintained under this condition for about 2h;
[0091] S3: After the reaction is completed, turn on the nitrogen control switch, slowly fill the three-necked flask with high-purity nitrogen to break the vacuum, turn off the nitrogen control switch, turn on the vacuum pump and agitator, control the absolute pressure in the flask to 70Pa, control the temperature of the reactants in the flask to 85℃, and react for about 2h to obtain the polyurethane resin.
[0092] S4: Add the polyurethane resin, propylene glycol methyl ether acetate and ZrO2 obtained in step S3 into a three-necked flask, turn on the heating device and the stirrer, and stir evenly.
[0093] The polyurethane resin is prepared by the reaction of phenyl isocyanate and polyoxypropylene glycol. Since the polyurethane resin has a high viscosity (>2000cps), it cannot be directly used for optical materials. Therefore, the raw materials of the polyurethane optical material in this comparative example are based on Example 7 and have a solvent component (propylene glycol methyl ether acetate).
[0094] Performance testing:
[0095] The resin compositions prepared in Examples 1 to 12 and Comparative Examples 1-3 were numbered 1-14, respectively. The optical materials numbered 1-14 were preheated at 100°C for 20 min and then tested for viscosity using a high-temperature viscometer. The optical materials numbered 1-14 were preheated at 100°C for 20 min, then placed in a constant temperature and humidity environment at 298K (25°C) and a relative humidity of 80% for 2 h, and the isocyanate groups were fully reacted and cross-linked using moisture (H2O) to prepare test samples. The viscosity of the test samples at 2000 mJ / cm2 was tested using an AGS-X universal testing machine. 2Elongation at break; For the test of yellowing resistance, the samples were placed in a UV aging test chamber and continuously illuminated for 7 days, and then the samples before and after illumination were measured to calculate the color difference ΔE; the water vapor transmission rate was tested at 25°C and 90% RH using a water vapor transmission rate tester of model AQUATRAN3; Stability test: After the optical materials No. 1-14 were left to stand for 30 days under natural conditions, the upper layer solution was taken and the refractive index was measured again according to the above refractive index determination method. The test results are shown in Table 1 below:
[0096] Table 1
[0097]
[0098] As can be seen from Table 1, compared with the currently used polyurethane resin optical materials, the optical material provided by the present invention has a lower viscosity while ensuring an optical property with a higher refractive index, does not require additional solvent addition, and is easy to mix and prepare. And compared with Examples 1-6, Example 9 and Examples 10-11, when the isocyanate structure contains a benzene ring, the obtained optical material has poor yellowing resistance. Compared with Examples 5, Example 8 and Example 9, it can be seen that when the isocyanate structure contains a ketone group, an optical material with better yellowing resistance is obtained. This may be because the ketone group forms an intermolecular force with the amine ester group in the polyurethane structure chain, thereby improving the regularity of the polyurethane structure, thereby improving the yellowing resistance and mechanical properties of the polyurethane optical material. By comparing Example 3 and Comparative Example 1, as well as Example 7 and Comparative Example 2, it can be seen that after the inorganic nanoparticles are mixed with the isocyanate monomer and the alcohol monomer component, the alcohol or amine monomer has a lower viscosity, which helps the dispersibility of the inorganic nanoparticles, and the polyols, polyamines, etc. are rich in active hydrogen groups, which are easier to form chemical bonds with the inorganic nanoparticles. After the polyurethane resin is prepared, the overall uniformity of the system is good. Therefore, after standing for 30 days, the refractive index changes very little, the optical properties are stable, and the storage performance is good.
[0099] The high refractive index optical material provided by the present invention can be used in a variety of electronic devices, such as light extraction layers of OLED display devices, optical films of liquid crystal display devices, and optical lenses (lenses) in optical systems of cameras, camcorders or smart phones.
[0100] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A polyurethane high-refractive optical material, characterized in that: The invention comprises the following raw materials in parts by weight: 15 to 30 parts of isocyanate, 10 to 20 parts of active hydrogen compound, 25 to 60 parts of inorganic nanoparticles, and 0.1 to 3 parts of catalyst; the isocyanate is selected from at least one of aliphatic isocyanate, alicyclic isocyanate, and aromatic isocyanate; and the active hydrogen compound is a polyol.
2. The polyurethane high-refractive optical material according to claim 1, characterized in that: The isocyanate has a structure shown in formula (1): wherein Ar is selected from unsubstituted or substituted C1-C5 alkyl, C1-C5 alkyl with ether bond block, keto group, hydroxyl group, etc. 15 Alkyl, C3-C 20 Cycloalkyl, C6-C 20 Aryl; the C6-C 20 The aryl group contains 1 to 3 benzene rings, which are connected by single bonds, C1-C3 alkyl groups or fused groups; n is an integer of 1 to 3.
3. The polyurethane high refractive optical material according to claim 2, characterized in that: The C1-C 15 The alkyl group is selected from propane, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, n-pentyl, 2-pentyl, 3-pentyl, isopentyl, neopentyl, hexyl, heptyl, octyl or nonane; the C3-C 20 The cycloalkyl group is selected from cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclononane, cyclodecane, cyclododecane, cyclotetradecane or cyclohexadecane; the C6-C 20 The aryl group is selected from a benzene ring, naphthalene, anthracene, biphenyl, diphenylmethane, diphenylethane or triphenylmethane.
4. A polyurethane high refractive optical material according to any one of claims 1 to 3, characterized in that: The polyol is at least one of polyester polyol and polyether polyol.
5. The polyurethane high-refractive optical material according to claim 1, characterized in that: The inorganic nanoparticles are selected from any one or more combinations of Si3N4, NiO, Al2O3, ZrO2, TiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, and Nd2O3.
6. The polyurethane high-refractive optical material according to claim 1, characterized in that: The catalyst is selected from one or more combinations of organic amine catalysts and organic metal catalysts; The organic amine catalyst is selected from at least one of triethylamine, triethylenediamine, N,N-dimethylcyclohexylamine, N,N-diethylpiperazine, triethanolamine, N,N-dimethylpyridine, and dimorpholine diethyl ether; The organic metal catalyst is selected from at least one of zinc isooctanoate, bismuth isooctanoate, dibutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, stannous oleate, stannous chloride, tetra-n-butyltin, hydroxytrimethyltin, and dibutyltin dilaurate.
7. The polyurethane high-refractive optical material according to claim 1, characterized in that: It also includes one or more combinations of antioxidants, tackifying resins, and chain extenders.
8. The polyurethane high-refractive optical material according to claim 7, characterized in that: The antioxidant is selected from at least one of antioxidant 264, antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, and 2,6-di-tert-butyl-4-methylphenol; The tackifying resin is selected from at least one of rosin, terpene resin, alkylphenolic resin, xylene resin, and rosin glycerol ester; The chain extender is selected from at least one of diethylene glycol, triethylene glycol, cyclohexanedimethanol, ethylene glycol, propylene glycol, hexanediol, butanediol, neopentyl glycol, triethylene glycol, dipropylene glycol, and ethyl hexanediol.
9. A method for preparing the polyurethane high-refractive optical material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, putting polyol and inorganic nanoparticles into a flask, heating while stirring, controlling the reaction temperature at 80-85°C, evacuating the flask to an absolute pressure of 50-100 Pa, continuing to heat to 120-130°C, and maintaining the reaction temperature and absolute pressure for 0.4-0.6h; then filling the flask with nitrogen to break the vacuum state, and cooling it to 80-85°C; S2, adding isocyanate and catalyst into a flask, evacuating the flask to an absolute pressure of 50-100 Pa, controlling the reaction temperature in the flask to 70-95° C., maintaining the pressure and temperature conditions and continuing the reaction for 1.5-3 hours; S3, after the reaction is completed, nitrogen is filled into the flask to break its vacuum state, and the flask is evacuated again until the absolute pressure in the flask is 50-100Pa, the reaction temperature in the flask is controlled to be 85-90°C, and the reaction is carried out for 1-3h to obtain a polyurethane high-refractive optical material.
10. Use of the polyurethane high-refractive optical material according to any one of claims 1 to 8 in preparing an optical material layer of a display device.